Pedagogical and medical aspects of health and fitness in the process of physical education of students of medical university - Johnson, Apamba Stephanie (Запорізький державний медичний університет, 2016)
To study the effectiveness of using fitness for the health of students, we conducted observation of two groups of students of 1-2 courses Zaporozhye state medical University. One of them is control group (CG) during physical education classes worked on the curriculum, the second group of observations (GN) engaged in health fitness, and systems for fitness of different coordination complexity were selected differentiated, depending on the level of development of coordination abilities and motor experiences of students. Students took a survey at the beginning and end of the school year conducted a comprehensive medical examination with determination of the level of physical health by A. L. Apanasenko.
Keywords: тези доповідей